2012
DOI: 10.1063/1.4769354
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Oscillated band gaps of B/N-codoped α-graphyne

Abstract: The physical mechanism for the electronic structures tuning and band gap opening of α-graphyne are investigated from the first principles calculations. The pathway of using B and N atoms to codope into graphyne is proposed. After codoping, B atom plays a role of hole doping and N atom acts as electron doping. In codoped graphyne, the Fermi energy returns around the Dirac point and a gap is introduced. Interestingly, the opened gaps oscillate periodically with the increasing distances between B and N atoms with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Approaches similar to those employed for graphene such as doping, diatomic molecules and cations intercalation, can be envisaged. 30 In the same spirit, tight-binding calculations have shown that the band gap of γ-graphyne may be tuned and that Dirac cones may appear if the triple bonds are artificially elongated. 11 In contrast, addition of HF and corresponding symmetry breaking, allows for opening of the band gap of α-graphyne.…”
Section: Resultsmentioning
confidence: 99%
“…Approaches similar to those employed for graphene such as doping, diatomic molecules and cations intercalation, can be envisaged. 30 In the same spirit, tight-binding calculations have shown that the band gap of γ-graphyne may be tuned and that Dirac cones may appear if the triple bonds are artificially elongated. 11 In contrast, addition of HF and corresponding symmetry breaking, allows for opening of the band gap of α-graphyne.…”
Section: Resultsmentioning
confidence: 99%
“…However, the γGYNR has been predicted to be semiconductors exhibiting small carrier effective masses and high carrier mobility like graphene [4]. Previous theoretical researches about dopant have also displayed intriguing electronic or transport properties of GYNR [49, 50, 54, 55]. Previous experimental investigations on the graphdiyne NRs [8, 9] and device without or with N-doping [56, 57] have also been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the unique physical properties of graphene, graphyne has also been predicted to exhibit unusual properties such as strong anisotropy of elastic, electronic, and optical properties, low fracture stress and Young's modulus, effective masses of charge carrier, and having versatile Dirac cones . Deng et al . used the B and N co‐doped graphyne as a model to investigate the band gap and the electronic structure, and found that the Fermi energy returns around the Dirac point.…”
Section: Introductionmentioning
confidence: 99%